Implementasi Pembelajaran Berbasis Multiliterasi dalam Mata Pelajaran Aqidah Akhlak di Kelas XI MTs Nurul Huda Jakarta Timur - Moh Alwy Al Maliki; Moh. Irmawan Jauhari; Suko Susilo (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to explore the implementation of multiliteracy-based learning in the Aqidah Akhlak subject for ninth-grade students at MTs Nurul Huda, East Jakarta. The research investigates how multiliteracy approaches are integrated into classroom instruction, the strategies used by teachers, the responses of students, and the challenges encountered during the process. Using a qualitative descriptive method, data were collected through classroom observations, interviews with teachers and students, and documentation analysis. The findings indicate that multiliteracy learning—encompassing linguistic, visual, digital, and cultural literacies—has been gradually adopted to enhance students’ understanding of moral and religious values. Teachers utilize various media and interactive activities, such as videos, group discussions, and contextual moral case studies, to engage learners. Students respond positively to these approaches, demonstrating improved participation and comprehension. However, challenges remain, particularly in terms of digital infrastructure and the need for ongoing teacher training. Overall, multiliteracy-based learning in Aqidah Akhlak contributes to more meaningful and relevant moral education by aligning content with students’ real-life experiences and the demands of the 21st century.